Effects of Vaccination on Invasive Pneumococcal Disease in South Africa - von Gottberg, Anne; de Gouveia, Linda; Tempia, Stefano; Quan, Vanessa; Meiring, Susan; von Mollendorf, Claire; Madhi, Shabir A; Zell, Elizabeth R; Verani, Jennifer R; O’Brien, Katherine L; Whitney, Cynthia G; Klugman, Keith P; et al. (The New England journal of medicine, 2014)
Invasive pneumococcal disease is an important cause of severe illness. In South Africa, a national program to vaccinate children with the conjugated pneumococcal vaccine resulted in a substantial decline in invasive pneumococcal disease countrywide, including in adults. The majority of deaths associated with childhood pneumococcal disease occur in Africa. 1 , 2 In randomized trials conducted in Africa, 3 , 4 a pneumococcal conjugate vaccine (PCV) was given to infants when they were 6, 10, and 14 weeks of age, without a booster dose. The vaccine showed efficacy for the prevention of invasive pneumococcal disease caused by the nine serotypes contained in the vaccine among infants who were not infected with the human immunodeficiency virus (HIV) (83% efficacy; 95% confidence interval [CI], 39 to 97) and among infants who were infected with HIV (65% efficacy; 95% CI, 24 to 86). 3 , . . .